2020
DOI: 10.1017/s0008423920000396
|View full text |Cite
|
Sign up to set email alerts
|

How Right-Leaning Media Coverage of COVID-19 Facilitated the Spread of Misinformation in the Early Stages of the Pandemic in the U.S.

Abstract: We have yet to know the ultimate global impact of the novel coronavirus pandemic. However, we do know that delays, denials and misinformation about COVID-19 have exacerbated its spread and slowed pandemic response, particularly in the U.S. (e.g., Abutaleb et al., 2020).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
230
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(245 citation statements)
references
References 5 publications
12
230
0
3
Order By: Relevance
“…Previous research found that right-wing politicians (Green et al, 2020) and media outlets (Motta et al, 2020) downplay the public health risks associated with COVID-19. In our data, beliefs about consequences of prophylactic measures for personal security were the strongest mediators between media consumption and compliance with CDC recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found that right-wing politicians (Green et al, 2020) and media outlets (Motta et al, 2020) downplay the public health risks associated with COVID-19. In our data, beliefs about consequences of prophylactic measures for personal security were the strongest mediators between media consumption and compliance with CDC recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, party affiliation of public officials is associated with differences in frequency and content of messaging on COVID-19: Democratic politicians discussed the pandemic more frequently and placed more focus on public health risks than the Republicans, and the Republicans discussed economic implications of the virus and China's role in its origins more frequently (Green et al, 2020). Partisan media similarly presented American viewers with conflicting messages (Bursztyn et al, 2020;Motta et al, 2020). Republican party affiliation and exposure to right-wing media have been shown to relate to lower compliance with CDC health recommendations regarding social distancing (Allcott et al, 2020;Andersen, 2020;Barrios & Hochberg, 2020;Simonov et al, 2020;Wright Correspondence should be addressed to Vladimir Ponizovskiy, 309 South Hall, Campus Ring 1, Bremen, Germany, 28759.…”
mentioning
confidence: 99%
“…Our analysis builds upon the recent work of scholars who find relationships between partisanship and public policy choices, citizen and elite attitudes/knowledge, and citizen and elite behaviour related to COVID-19 (Armstrong and Lucus, 2020;Gadarian et al, 2020;Merkley et al, 2020;Miller, 2020;Motta et al, 2020;Pickup et al, 2020;van der Linden and Savoie, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Then participants were asked, "Based on what you've read, seen or heard in the past week, how much disagreement do you think there is about the following aspects of COVID-19 (coronavirus) among health experts: i) Who is most at risk of being infected with COVID-19 (coronavirus); ii) How dangerous it is for someone to become infected with COVID-19 (coronavirus); iii) Whether there is adequate access to testing for COVID-19 (coronavirus); and iv) Whether the drugs chloroquine and hydroxychloroquine are effective in treating COVID-19 (coronavirus)." For each aspect, response options included "No disagreement" (1), "A little disagreement" (2), "Some disagreement" (3), and "A lot of disagreement" (4). Again referencing what they read, saw, or heard in the past week, participants were asked, "How much disagreement do you think there is among health experts about the effectiveness of the following strategies for preventing the spread of COVID-19 (coronavirus): i) Keeping 6 feet away from other people, except those you live with; ii) Wearing a mask or other face covering when out in public; iii) Keeping schools closed; iv) Keeping all businesses closed except those considered essential (e.g., grocery stores, pharmacies); v) Self-quarantining when sick; and vi) Washing your hands with soap several times per day."…”
Section: Methodsmentioning
confidence: 99%
“…The rapid spread of inaccurate information and conspiracy theories about COVID-19 via social media and in other spaces poses a clear threat to public understanding and decision making. Yet while much attention to date has been directed toward documenting and combatting such misinformation [2][3][4][5], another aspect of the infodemic has been relatively overlooked: conflicting information surrounding COVID-19. Whereas misinformation refers to false information that is shared either knowingly or accidentally (e.g., wearing a mask can cause deadly rebreathing of exhaled carbon dioxide) [6], conflicting information has been defined as two or more health-related propositions that are logically inconsistent with one another (e.g., wearing a mask does versus does not help prevent viral transmission) [7].…”
Section: Introductionmentioning
confidence: 99%